The influence of morphology and crystal orientation of spangles on hot-dip Zn-0.5Sn alloy coating - Zhai L.; Peng H -P.; Liu Y.; Lei Y.; Deng S.; Su X.-P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The study on the surface morphology and crystal orientation of the Zn-0.5Sn coating could offer some guidance to improve the surface performance of the hot-dip galvanizing coating. In this paper, a scanning electron microscope (SEM) and an energy dispersive spectrometer (EDS) were used to analyze the typical morphology and the element distribution of spangles. The surface texture of the coating was analyzed by X-ray diffraction (XRD). Electron backscatter diffraction (EBSD) was used to analyze the crystal orientation of spangles. The results show that Sn segregates among the spangle dendrites while a metastable divorced eutectic structure can be maintained in the tin-rich phase, where the composition tends to be very similar. The crystal orientation of spangles affects their morphology, leading to the formation of feathery, ridged, and orthogonal dendrite arm spangles. When the angle among the <0001> orientation of the spangle crystal and the normal of the steel base surface changes from 0° to 90°, feathery spangles change to orthogonal dendrite arms spangles. The misorientation within a spangle is small while that among spangles is quite large. The orientation changes in the direction of the dendrite arm are relatively smooth and low, while the orientation changes which are perpendicular to the dendrite arm have a saltatory and irregular fluctuation.